Influence of choice of priority functions on the multi criteria ranking result - Podvezko, Valentinas; Podviezko, Askoldas (Lietuvos matematikos rinkinys, 2009)
PROMETHEE method differs from other methods by its deeper logic. The main tool of the method is so-called priority functions. Choice of functions and their parameters is made by decision-makers. PROMETHEE method provides a choice between a large range of functions, thus allowing to perfectly match decision-maker’s opinion. This paper shows dependency of outranking result on the choice of priority functions.